A selective small molecule NOP (ORL-1 receptor) partial agonist for the treatment of anxiety. Issue 3 (1st February 2015) - Ross, Tina Morgan; Battista, Kathleen; Bignan, Gilles C.; Brenneman, Doug E.; Connolly, Peter J.; Liu, Jingchun; Middleton, Steven A.; Orsini, Michael; Reitz, Allen B.; Rosenthal, Dan I.; Scott, Malcolm K.; Vaidya, Anil H.
Graphical abstract